PENGARUH FANATISME, GAYA HIDUP HEDONIS, DAN PERSEPSI KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK IPHONE DI INDONESIA - Hesti Ayu Lestari; Ginanjar Rahmawan (Jurnal Ilmu Manajemen, 2023)
Technological developments in smartphones make it easier for someone to carry out their activities and lead to a hedonic lifestyle because they are more concerned with brands than functions. This study examines the attitude of fanaticism, hedonic lifestyle, and consumer perceptions of the purchasing decisions of iPhone product users in Indonesia. The population in this study are iPhone product users in Indonesia, with a large sample of 170 respondents. The sampling technique uses purposive sampling by determining the sample criteria. This study uses a quantitative approach. The data used in this research are primary data via a questionnaire with a Google Form link and secondary data sourced from interviews and various literature. Then the results of this study were processed using SPSS. Fanaticism, hedonic lifestyle, and consumer perceptions significantly affect purchasing decisions. The results of this study also show that fanaticism, hedonic lifestyle, and consumer perceptions shape consumer desires in purchasing iPhone products.